2009
DOI: 10.1063/1.3061462
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the effects of the charge state and size of gold clusters on the adsorption and dissociation of H2

Abstract: The adsorption and dissociation of H(2) on the neutral and charged gold clusters Au(n) (m)(m=0,+/-1; n=1-6) is investigated using the density functional theory PW91 functional. H(2) interacts very weakly with Au(n) (-1), whereas the interaction with Au(n) (+1) is relatively strong. The binding energies on neutral clusters are between those on the cationic and anionic systems. The binding energy decreases monotonically with the size increase of the cationic clusters while it goes up first and then goes down on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 33 publications
1
40
0
1
Order By: Relevance
“…Figures 6a and 6b demonstrate that H 2 can dissociate on the neutral Au 3 and Au 4 clusters with a very low barrier, for both T = 0 K and T = 298.15 K. However, for n = 2 and 5−11 the energy of the TS state is considerably larger than the binding Therefore, it is likely that molecular H 2 will desorb from Au 2 and Au 5−11 , rather than dissociate. On the basis of PW91/def2-TZVPP DFT calculations, 56 Kang et al suggested that H 2 dissociation is also feasible on the Au 5 cluster because the binding energy of H 2 to Au 5 is larger than the dissociation barrier. However, according to our calculations with the use of PBE functional with DZP basis set, the barrier is larger than the change in free energy upon H 2 adsorption on Au 5 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Figures 6a and 6b demonstrate that H 2 can dissociate on the neutral Au 3 and Au 4 clusters with a very low barrier, for both T = 0 K and T = 298.15 K. However, for n = 2 and 5−11 the energy of the TS state is considerably larger than the binding Therefore, it is likely that molecular H 2 will desorb from Au 2 and Au 5−11 , rather than dissociate. On the basis of PW91/def2-TZVPP DFT calculations, 56 Kang et al suggested that H 2 dissociation is also feasible on the Au 5 cluster because the binding energy of H 2 to Au 5 is larger than the dissociation barrier. However, according to our calculations with the use of PBE functional with DZP basis set, the barrier is larger than the change in free energy upon H 2 adsorption on Au 5 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…These small clusters are selected because Au n clusters with n =3-5 are found most active. 28 We examined the adsorption of ethylene and formaldehyde on these clusters. Our results demonstrate that ethylene and formaldehyde can interact moderately strongly with Au clusters with binding energies higher than those previously reported.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that adsorption simultaneously results in the structural deformation of both the adsorbate and the cluster, which will destabilize the adsorption system. Previously [22,35] we have adopted E int defined in (1) to estimate the interaction between an adsorbate and a cluster:…”
Section: Methodsmentioning
confidence: 99%